Improving the Quality of Transport Services Logistics Approach - Saparbaevna, Atadzhanova Zulfiya; Amanovna, Kadirova Sharafat (International Journal of Psychosocial Rehabilitation, 2020)
This Article Is Based On The Theoretical Aspect Of Determining The Omillarni That Should Be Taken Into Account When Assessing The Quality Of Transport Services And Methods Of Studying Their Applicable Level As Well As The Impact On The Development Of Railway Activities.